Evaluation of lentil varieties for adaptation and yield performance under midland ecology of kaffa zone, south-west Ethiopia - Geja, MM (International Journal of Agricultural Research, Innovation and Technology, 2020)
A field experiment was conducted to identify the best adapted and high yielding lentil variety at Shishinda sub-testing site of Bonga Agricultural Research Center during 2012 main cropping season. The experiment was carried out in randomized complete block design with three replications. Eleven improved lentil varieties were used for this study. The varieties included in the study were Teshale, Alemaya, Alemtena, Assano, Gudo, EL-142, R-186, Ada’a, Derso, Chalew and Chekol. The parameters studied in this experiment were days to flowering and maturity, plant height, number of pods plant-1, number of seeds pod-1, thousand seeds weight and grain yield. The analysis of the experiment showed significant (p<0.05) differences among varieties for all studied parameters. The varieties Assano, Alemtena, Derso, EL-142, and Gudo were found to be high yielder with the value of 1.71, 1.59, 1.39, 1.36 and 1.31 ton ha-1, respectively. In addition, farmers were invited to evaluate the performance of the tested varieties under field condition. Eventually, the farmers selected Assano and Alemtena as the most preferred varieties. Therefore, these varieties can be suggested to use for wider production in the study area. The involvement of farmers in variety selection processes may increases the adoption of new variety in the area. Int. J. Agril. Res. Innov. Tech. 9(2): 9-14, December 2019